2022
DOI: 10.1186/s12934-022-01791-8
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological potential and initial characterization of two novel sesquiterpene synthases from Basidiomycota Coniophora puteana for heterologous production of δ-cadinol

Abstract: Background Terpene synthases are versatile catalysts in all domains of life, catalyzing the formation of an enormous variety of different terpenoid secondary metabolites. Due to their diverse bioactive properties, terpenoids are of great interest as innovative ingredients in pharmaceutical and cosmetic applications. Recent advances in genome sequencing have led to the discovery of numerous terpene synthases, in particular in Basidiomycota like the wood rotting fungus Coniophora puteana, which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Its structure factors and atomic coordinates have been deposited in the Protein Data Bank with accession number 8GY0. The overall structure is a typical class I TPS where the α-domain contains two conserved metal-ion coordination motifs ( 84 DEXXD 88 and 219 NSE 227 ) as well as the 302 WXXXXXRY 309 motif known to be close to the active site via salt bridge formation upon substrate binding . As TPSs are known to be inactive in the absence of Mg 2+ ions, structural determination/analysis and molecular modeling were carried out by using the structure of Ap.LS* obtained in the presence of Mg 2+ .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Its structure factors and atomic coordinates have been deposited in the Protein Data Bank with accession number 8GY0. The overall structure is a typical class I TPS where the α-domain contains two conserved metal-ion coordination motifs ( 84 DEXXD 88 and 219 NSE 227 ) as well as the 302 WXXXXXRY 309 motif known to be close to the active site via salt bridge formation upon substrate binding . As TPSs are known to be inactive in the absence of Mg 2+ ions, structural determination/analysis and molecular modeling were carried out by using the structure of Ap.LS* obtained in the presence of Mg 2+ .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The crystal structure of AcCop4 was determined by the molecular replacement method using Phaser in the PHENIX package . The coordinates of Copu9 (PDB code: 7OFL) were used as the search model. The initial structure was refined with iterative cycles of simulated annealing, energy minimization, and manual rebuilding using PHENIX refinement and COOT .…”
Section: Methodsmentioning
confidence: 99%
“…Structural Comparison of AcCop4 with Its Homologs. Based on a DALI analysis, AcCop4 shares a high structural similarity with a group of class I terpenoid cyclase members with very low sequence identity, including Copu9 (PDB code: 7OFL, Z-score: 42.1, 36% identity), 25 selinadiene synthase (PDB code: 4OKM, Z-score: 34.6, 20% identity), 31 epiisozizaene synthase (PDB code: 3KB9, Z-score: 33.7, 20% identity), 32 and pentalenene synthase (PDB code: 6WKD, Zscore: 32.3, 23% identity). 33 Except for the α-helical class I terpenoid cyclase fold, AcCop4 and Copu9 possess an additional unique two-stranded β-sheet.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…It suggested that the helix-turn-helix motif may be a hot spot for product-shifting mutations and thus serve as a guide for improving related class I products. 55 W279 is on the C helix of the CS and toward the bottom of the active site cleft. The larger volume of residue at position 279 extended the channel that allowed water access to the active site, increasing the ratio of alcohol to hydrocarbon products.…”
Section: Application Of Site-directed Mutagenesis In Stssmentioning
confidence: 99%
“…Similarly, mutations of the corresponding glycine and cysteine (G186 and C187) residues in COS2, both of which are located in the conserved “kink” region between the α-helices G1 and G2, altered the product profile from (+)-δ-cadinol to germacrene D-4-ol. It suggested that the helix-turn-helix motif may be a hot spot for product-shifting mutations and thus serve as a guide for improving related class I products …”
Section: Application Of Site-directed Mutagenesis In Stssmentioning
confidence: 99%